BRAIT, BETH (2010). Literatura e outras linguagens - Miotello, Valdemir; Haber de Figueiredo, Marina (Revista Latinoamericana de Estudios del Discurso, 2020)
BRAIT, BETH (2010). Literatura e outras linguagens. São Paulo: Contexto. 235 pp. ISBN 978-85-7244-489-7.